1990
DOI: 10.1089/aid.1990.6.371
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Secreted, Native gp120 and gp160 of the Human Immunodeficiency Virus Type 1

Abstract: We have previously shown that the cell line 6D5(451) chronically infected with the HIV-1 isolate HTLV-III(451), secretes the HIV-1 envelope glycoproteins gp120 and gp160 in the extracellular medium. The HTLV-III(451) gp120 and gp160 were purified by sequential affinity chromatographic steps using a monoclonal antibody to HIV-1 gp41 and an anti-HIV-1-positive human serum. Amino acid sequence analysis of gp120 and gp160 showed the loss of the signal peptide. Digestion of the purified gp120 and gp160 with endogly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 24 publications
0
49
0
Order By: Relevance
“…4 An additional Ad5hr-SIVgag recombinant carrying a rev-independent SIV mac239 gag gene (33) has been described elsewhere. 3 Native gp120 was purified from a productive tissue culture medium as previously described for HIV-1 gp120 (34). An SIV polypeptide representing covalently joined repeating 18-mer amino acid segments homologous to the CD4 binding region of SIV mac251 gp120 was synthesized as previously described (20,35,36).…”
Section: Recombinant and Subunit Immunogensmentioning
confidence: 99%
“…4 An additional Ad5hr-SIVgag recombinant carrying a rev-independent SIV mac239 gag gene (33) has been described elsewhere. 3 Native gp120 was purified from a productive tissue culture medium as previously described for HIV-1 gp120 (34). An SIV polypeptide representing covalently joined repeating 18-mer amino acid segments homologous to the CD4 binding region of SIV mac251 gp120 was synthesized as previously described (20,35,36).…”
Section: Recombinant and Subunit Immunogensmentioning
confidence: 99%
“…The neutralization epitopes that are functional on primary envelopes tend to be conformation dependent (9,16,40). Accessibility of some of the epitopes depends on conformational changes that occur after engagement of CD4 (39,40).…”
mentioning
confidence: 99%
“…'Spontaneous' secretion of gp160 by a chronically infected cell line (Kalyanaraman et al, 1988(Kalyanaraman et al, , 1990, and more recently secretion of a similarly truncated gpl60 (Hallenberger et al, 1993;Owens et al, 1994), have also been reported. In addition, unprocessed gpl60 may also be present on virions, especially when the cytoplasmic tail is shortened due to insertion of a translational stop in the env gene (Dubay et al, 1992).…”
Section: Hiv-1 Chronic Infection 2967mentioning
confidence: 92%